Evaluation of the Efficacy of Yavanna (Rajaswala Paricharya diet) versus Routine Care in the Management of Kashtartava (Primary Dysmenorrhoea): A Randomised Controlled Trial Protocol - Niharika Sharma; Pradnya Dandekar (Journal of Clinical and Diagnostic Research)
Introduction: Menstrual pain is a common problem among women of reproductive age, negatively affecting their daily activities and quality of life. In Ayurveda, a classic diet and lifestyle regimen is recommended during menstruation, known as Rajaswala Paricharya. Adhering to this diet during menstruation in otherwise healthy women is thought to produce shuddhaartava (i.e., a painless, healthy menstrual cycle). Aim: To assess the efficacy of the Rajaswala Paricharya diet (Yavanna – barley porridge diet) compared to routine care (Mefenamic acid) in cases of primary dysmenorrhoea. Need of the study: Modern medical treatments for dysmenorrhoea (primary dysmenorrhoea) include Non Steroidal Anti-Inflammatory Drugs (NSAIDs) and oral contraceptives, which may produce certain side-effects such as gastrointestinal disturbances, stomach ulcers, and allergic reactions. Therefore, the present study aims to develop a treatment that is simple to administer, highly effective in alleviating the condition and has minimal or no side-effects, ensuring patient acceptance. Materials and Methods: A single-centre, randomised, single-blinded, parallel-group controlled trial will be conducted at MGACH, Wardha, Maharashtra, India, over three consecutive cycles (a three-month period) from July 2024 to March 2025. The subjects will be divided into two groups: the control group and the experimental group. The experimental group will follow the Rajaswala Paricharya diet (Yavanna) by consuming 100-250 grams of barley per day in two divided meals, according to appetite, as the intervention. The control group will take a tablet of mefenamic acid at 250 mg twice daily during menstruation for three consecutive cycles. Patients will be assessed for pain using changes in the Working ability, Location, Intensity, Days of pain, Dysmenorrhea (WaLIDD) score and the Visual Analog Scale (VAS) score on the first three days of the menstrual cycle over four consecutive cycles (the first cycle after registration for baseline assessment followed by three consecutive cycles for after-treatment assessment). Statistical analysis will be conducted using a paired t-test and Chi-square test, with statistical significance set at p-value ≤0.05.